The Influence of Service Quality, Customer Experience, Perceived Value, and Brand Trust on Customer Loyalty in Digital Service Platform - Milcha Handayani Tammubua; Irwan Ardiansah; Sugeng Riyadi; Reza Fauzi Nazar (Malaqbi Publisher, 2026)
The rapid growth of digital service platforms has intensified competition among service providers, making customer loyalty a critical factor for achieving long-term business success. This study aims to examine the influence of service quality, customer experience, perceived value, and brand trust on customer loyalty in digital service platforms. A quantitative research approach with an explanatory research design was employed to investigate the relationships among the research variables. Data were collected through a structured questionnaire using a five-point Likert scale and distributed to users of digital service platforms through purposive sampling. The collected data were analyzed using descriptive statistics, reliability testing, validity testing, and multiple linear regression analysis. The findings indicate that service quality, customer experience, perceived value, and brand trust each have a positive and significant influence on customer loyalty. Simultaneously, these four variables significantly explain customer loyalty, indicating that they collectively contribute to customers' intentions to continue using digital service platforms. Among the independent variables, brand trust was identified as the strongest predictor of customer loyalty, followed by customer experience, service quality, and perceived value. These findings suggest that fostering customer loyalty requires organizations to focus not only on delivering high-quality services but also on creating positive customer experiences, enhancing customers' perceived value, and building strong brand trust through reliable and secure digital services. The study contributes to the marketing and consumer behavior literature by providing empirical evidence regarding the determinants of customer loyalty in digital service platforms and offers practical implications for managers seeking to improve customer retention and long-term business performance.